In the (Very) Long Run We Are All Dead: Activation and Termination in SET-LRP/SARA-ATRP - Harrisson, Simon; Nicolas, Julien (ACS macro letters, 2014)
The rate constants of activation and termination were determined for SET-LRP/SARA-ATRP polymerizations of methyl acrylate. Measurement of the rate of generation of CuBr throughout the reaction (using data from Levere et al., , , 8267-8274) allowed evaluation of the chain length dependence of the two rate constants, which were found to be 1.25(9) × 10 DP cm·s (activation) and 3.1(1) × 10 DP L·mol ·s (termination). Addition of the CuBr deactivator at the beginning of the reaction is found to result in a higher proportion of dead chains due to rapid termination of short chains.